Efficient hepatic differentiation and regeneration potential under xeno-free conditions using mass-producible amnion-derived mesenchymal stem cells - Jiwan Choi (BMC, 2021)
Abstract Background Amnion-derived mesenchymal stem cells (AM-MSCs) are an attractive source of stem cell therapy for patients with irreversible liver disease. However, there are obstacles to their use due to low efficiency and xeno-contamination for hepatic differentiation. Methods We established an efficient protocol for differentiating AM-MSCs into hepatic progenitor cells (HPCs) by analyzing transcriptome-sequencing data. Furthermore, to generate the xeno-free conditioned differentiation protocol, we replaced fetal bovine serum (FBS) with polyvinyl alcohol (PVA). We investigated the hepatocyte functions with the expression of mRNA and protein, secretion of albumin, and activity of CYP3A4. Finally, to test the transplantable potential of HPCs, we transferred AM-MSCs along with hepatic progenitors after differentiated days 11, 12, and 13 based on the expression of hepatocyte-related genes and mitochondrial function. Further, we established a mouse model of acute liver failure using a thioacetamide (TAA) and cyclophosphamide monohydrate (CTX) and transplanted AM-HPCs in the mouse model through splenic injection. Results We analyzed gene expression from RNA sequencing data in AM-MSCs and detected downregulation of hepatic development-associated genes including GATA6, KIT, AFP, c-MET, FGF2, EGF, and c-JUN, and upregulation of GSK3. Based on this result, we established an efficient hepatic differentiation protocol using the GSK3 inhibitor, CHIR99021. Replacing FBS with PVA resulted in improved differentiation ability, such as upregulation of hepatic maturation markers. The differentiated hepatocyte-like cells (HLCs) not only synthesized and secreted albumin, but also metabolized drugs by the CYP3A4 enzyme. The best time for translation of AM-HPCs was 12 days from the start of differentiation. When the AM-HPCs were transplanted into the liver failure mouse model, they settled in the damaged livers and differentiated into hepatocytes. Conclusion This study offers an efficient and xeno-free conditioned hepatic differentiation protocol and shows that AM-HPCs could be used as transplantable therapeutic materials. Thus, we suggest that AM-MSC-derived HPCs are promising cells for treating liver disease.